Framing AI Ethics in Public Discourse: A Critical Discourse Analysis of Media Coverage on AI in Child Protection - Emasealu, Victoria Imariaikowa (Yayasan Ilomata, 2024)
Objectives: This study aims to examine the framing of AI ethics in U.S. media coverage of child protection technologies, focusing on efforts to combat online exploitation. The research seeks to analyze evolving narratives and ethical considerations surrounding AI in this sensitive domain. Methods: The study employs critical discourse analysis to examine 30 articles from major U.S. news outlets published between 2018 and 2023. This approach allows for an in-depth exploration of media framing, stakeholder representation, and the evolution of ethical discussions over time. Findings and conclusions: The research reveals a shift from initial technological solutionism to more nuanced discussions of ethical dilemmas in AI-driven child protection efforts. Key findings include: (1) highlighted tensions between privacy and protection, (2) concerns about false positives and overreach, (3) issues of transparency and fairness, and (4) patterns in stakeholder representation, including the marginalization of children's and families' voices. The study concludes that media framing significantly influences public perception and policy responses to AI in child protection. It emphasizes the need for a diverse, inclusive, and ethically-grounded public discourse to guide the responsible development and deployment of AI technologies in this field.